Coordination behavior of dimethyl pyridine-2, 6-dicarboxylate towards mercury(II), cadmium(II) and chromium(III) in the solid- and gaseous state supported by CSD studies. (14th December 2015) - Hakimi, Mohammad; Mardani, Zahra; Moeini, Keyvan; Mohr, Fabian
Graphical abstract: Three complexes of dimethyl pyridine-2, 6-dicarboxylate (MPC) including [Hg(MPC)Cl2 ] (1 ), [Cd(MPC)3 ][CdBr4 ] (2 ) and a coordination polymer, K[Cr(PDC)2 ] n (3 ) were prepared and identified by elemental analysis, FT-IR, Raman, 1 H NMR spectroscopies and single-crystal X-ray diffraction. All coordination modes of MPC derivatives were studied by CSD and then optimized by DFT. A new formula for determination of geometry around the metals with coordination number four is presented. Abstract: In this work, three complexes, [Hg(MPC)Cl2 ] (1 ), [Cd(MPC)3 ][CdBr4 ] (2 ) and the coordination polymer, K[Cr(PDC)2 ] n (3 ) of dimethyl pyridine-2, 6-dicarboxylate (MPC) and hydrolyzed MPC, pyridine-2, 6-dicarboxylic acid (H2 PDC), were prepared and identified by elemental analysis, FT-IR, Raman, 1 H NMR spectroscopy and single-crystal X-ray diffraction. All coordination modes of dimethyl pyridine-2, 6-dicarboxylate derivatives were studied by CSD to predict the behavior of MPC in reactions with metals. Subsequently, these coordination modes were optimized by DFT methods to determine of the most stable mode and charge distribution. In the crystal structure of1, the mercury atom has a HgNO2 Cl2 environment and inclines to a trigonal bipyramidal geometry. The molecule of2 has two cadmium atoms with different geometries. One Cd atom has coordination number four and ideal tetrahedral geometry which is determined by using a new formula proposed in this paper. The crystal structure of3 revealed a rare 2D s – d mixed-metal coordination polymer containing dodecahedrally coordinated potassium(I) and octahedral chromium(III). Common coordination number for mercury(II), cadmium(II) and chromium(III) is determined by studying of all complexes of them in CSD.